Factors Associated with Unplanned Primary Cesarean Birth: Secondary Analysis of the Listening to Mothers in California Survey - Carol Sakala; Candice Belanoff; Eugene R. Declercq (BMC, 2020)
Abstract Background In many countries, cesarean section has become the most common major surgical procedure. Most nations have high cesarean birth rates, suggesting overuse. Due to the excess harm and expense associated with unneeded cesareans, many health systems are seeking approaches to safe reduction of cesarean rates. Surveys of childbearing women are a distinctive and underutilized source of data for examining factors that may contribute to cesarean reduction. Methods To identify factors associated with unplanned primary cesarean birth, we carried out a secondary analysis of the Listening to Mothers in California Survey, limited to the subgroup who had not had a previous cesarean birth and did not have a planned primary cesarean (n = 1,964). Participants were identified through birth certificate sampling and contacted initially by mail and then by telephone, text message and email, as available. Sampled women could participate in English or Spanish, on any device or with a telephone interviewer. Following bivariate demographic, knowledge and attitude, and labor management analyses, we carried out multivariable analyses to adjust with covariates and identify factors associated with unplanned primary cesarean birth. Results Whereas knowledge, attitudes, preferences and behaviors of the survey participants were not associated with having an unplanned primary cesarean birth, their experience of pressure from a health professional to have a cesarean and a series of labor management practices were strongly associated with how they gave birth. These practices included attempted induction of labor, early hospital admission, and labor augmentation. Women's reports of pressure from a health professional to have a primary cesarean were strongly related to the likelihood of cesarean birth. Conclusions While women largely wish to avoid unneeded childbirth interventions, their knowledge, preferences and care arrangement practices did not appear to impact their likelihood of an unplanned primary cesarean birth. By contrast, a series of labor management practices and perceived health professional pressure to have a cesarean were associated with unplanned primary cesarean birth. Improving ways to engage childbearing women and implementing changes in labor management and communication practices may be needed to reduce unwarranted cesarean birth.